The disruptive – and beneficial – effects of distraction on older adults’ cognitive performance - Weeks, Jennifer C.; Hasher, Lynn (Frontiers in Psychology, 2014)
Older adults’ decreased ability to inhibit irrelevant information makes them especially susceptible to the negative effects of simultaneously occurring distraction. For example, older adults are more likely than young adults to process distraction presented during a task, which can result in delayed response times, decreased reading comprehension, disrupted problem solving, and reduced memory for target information. However, there is also some evidence that the tendency to process distraction can actually facilitate older adults’ performance when the distraction is congruent with the target information. For example, congruent distraction can speed response times, increase reading comprehension, benefit problem solving, and reduce forgetting in older adults. We review data showing that incongruent distraction can harm older adults’ performance, as well as evidence suggesting that congruent distraction can play a supportive role for older adults by facilitating processing of target information. Potential applications of distraction processing are also discussed.